Ultrafast Thermalization Pathways of Excited Bulk and Surface States in the Ferroelectric Rashba Semiconductor GeTe - Clark, Oliver J. (2022)
A large Rashba effect is essential for future applications in spintronics. Particularly attractive is understanding and controlling nonequilibrium properties of ferroelectric Rashba semiconductors. Here, time- and angle-resolved photoemission is utilized to access the ultrafast dynamics of bulk and surface transient Rashba states after femtosecond optical excitation of GeTe. A complex thermalization pathway is observed, wherein three different timescales can be clearly distinguished: intraband thermalization, interband equilibration, and electronic cooling. These dynamics exhibit an unconventional temperature dependence: while the cooling phase speeds up with increasing sample temperature, the opposite happens for interband thermalization. It is demonstrated how, due to the Rashba effect, an interdependence of these timescales on the relative strength of both electron-electron and electron-phonon interactions is responsible for the counterintuitive temperature dependence, with spin-selection constrained interband electron-electron scatterings found both to dominate dynamics away from the Fermi level, and to weaken with increasing temperature. These findings are supported by theoretical calculations within the Boltzmann approach explicitly showing the opposite behavior of all relevant electron-electron and electron-phonon scattering channels with temperature, thus confirming the microscopic mechanism of the experimental findings. The present results are important for future applications of ferroelectric Rashba semiconductors and their excitations in ultrafast spintronics.